Nanostructured Back Reflectors for Efficient Colloidal Quantum‐Dot Infrared Optoelectronics. Issue 33 (21st June 2019) - Baek, Se‐Woong; Molet, Pau; Choi, Min‐Jae; Biondi, Margherita; Ouellette, Olivier; Fan, James; Hoogland, Sjoerd; García de Arquer, F. Pelayo; Mihi, Agustín; Sargent, Edward H.
Abstract: Colloidal quantum dots (CQDs) can be used to extend the response of solar cells, enabling the utilization of solar power that lies to the red of the bandgap of c‐Si and perovskites. To achieve largely complete absorption of infrared (IR) photons in CQD solids requires thicknesses on the micrometer range; however, this exceeds the typical diffusion lengths (≈300 nm) of photoexcited charges in these materials. Nanostructured metal back electrodes that grant the cell efficient IR light trapping in thin active layers with no deterioration of the electrical properties are demonstrated. Specifically, a new hole‐transport layer (HTL) is developed and directly nanostructured. Firstly, a material set to replace conventional rigid HTLs in CQD devices is developed with a moldable HTL that combines the mechanical and chemical requisites for nanoimprint lithography with the optoelectronic properties necessary to retain efficient charge extraction through an optically thick layer. The new HTL is nanostructured in a 2D lattice and conformally coated with MoO3 /Ag. The photonic structure in the back electrode provides a record photoelectric conversion efficiency of 86%, beyond the Si bandgap, and a 22% higher IR power conversion efficiency compared to the best previous reports. Abstract : A colloidal‐quantum‐dot (CQD) solar cell with a patterned organic hole‐transport layer responsible for efficient light trapping in the near infrared is presented. The designed nanoimprinted organic structure gives the device efficient backscattering electrodes that lead to a 22% power conversion efficiency increase, achieving power conversion efficiencies of 1.34% in the near infrared, beyond Si absorption.